Design and Experiment of a New Type of Multi-position Rehabilitation Training Lower Limb Exoskeleton - Guoxin Xu; Bingqi Jia; Xiao Wei; Wenlong Bi; Huaqiang Zhang; Yanjun Zhao (Jixie chuandong)
The medical rehabilitation training equipment exists the problem that training method of is too single. A new type of multi-position rehabilitation training lower limb exoskeleton is designed， a mathematical model of the lower limb exoskeleton is established， and kinematics simulation and analysis are carried out. A multi-position lower limb rehabilitation exoskeleton experimental platform is built， and a gait walking experiment based on a physical prototype model is carried out. The simulation data and the experimental data are compared， it shows the correctness and rationality of the multi-position lower limb exoskeleton design.